GE_GERICHTE C/24893/2016 vom 24. Mai 2017 - GE Cour de justice (2017)
COMMINATION DE FAILLITE ; DROIT D'ÊTRE ENTENDU ; MOTIVATION DE LA DÉCISION ; DÉCISION DE RENVOI | LP.174.1; LP.174.2; Cst.29.2; CPC.53;